Grain sorting effects on geochemical characteristics of sulfide mine tailings: a case study - J C Arranz-González; V Cala-Rivero (Journal of Degraded and Mining Lands Management, 2017)
The geochemical evolution of a sulfide mine tailings impoundment in SW Spain was studied. The impoundment was selected because of its small size and its tailings deposition system with a simple discharge point. The objective of this study was to test the hypothesis that mineral segregation associated to hydraulic sorting has significant effects on the geochemical characteristics and the long term weathering. Tailings samples were collected along depth profiles in three sampling points (proximal, central and distal to the point of discharge), and characterized by color, grain size, pH, acid-base account and chemical elements concentration, with the help of routine XRD analysis. Three vertical zones were identified: an upper oxidized zone, a transition intermediate zone, and an unoxidized zone. The analytical results indicate a segregation pattern in the unoxidized tailings based on differences in size and density of tailings grains. Near the discharge point, tailings were coarser and rich in pyrite, whereas the proportion of silicates increased from proximal to distal points. This results in a clear zoning which has consequences on geochemical and mineralogical evolution under weathering, showing substantial differences in the depth of the oxidation front, the acid generation and neutralization capacity, the formation of Fe secondary phases (jarosite) and the total content of the sulfide-related elements (Fe, As, Zn, Cu, Pb and Cd). The results of the study can serve to improve the theoretical bases for the development of conceptual models for predicting environmental impacts associated with sulfide tailings impoundments. Recently, the impoundment has been covered with a soil cover. This fact offers the possibility of new research on its evolution under new conditions.